The contingency of neighbourhood diversity: Variation of social context using mobile phone application data. (March 2022) - Xu, Wenfei
This research uses high-density anonymised mobile phone application (MPA) global-positioning system (GPS) data to describe exposure to racial diversity in different social contexts with an aim to clarify the mechanism linking residential diversity to opportunities for diverse social interactions. In particular, it explores the hypothesis that a diverse residential context does not lead to diverse social contact by comparing three exposure measures – residential, observed and interaction – on the census block group level in Chicago. In doing so, it also explores the contribution of activity spaces to opportunities for diverse social contact. The findings show that the exposure to opportunities for diverse social contact measured by MPA data is generally higher than what is implied by residential census data, especially in areas of high residential segregation in the city. Further, measures using MPA data reveal more spatiotemporal heterogeneity of exposure than that implied by the residential context.